Empirical Study on the Browsing Behavior of PUGC Content among College Students in Anhui Province: Taking the Bilibili Blogger "MediaStorm" as an Example - Chai, Yi; Liu, Hongyang (International Journal of Social Sciences and Public Administration, 2025)
As major mainstream video platforms enter the PUGC construction, the creation mode that meets the audience’s interests and popularizes scientific knowledge is widely sought after. Under this trend, the academic and industry research on PUGC construction focuses more on economic benefits, business models and other objects, and pays less attention to the factors affecting audience behavior. User feedback is an important part of the interactive model of mass communication. This paper selects college students from Anhui universities as the research group to deeply understand young people’s cognition of "MediaStorm", a well-known PUGC creator on bilibili, analyze the factors affecting young people’s browsing of PUGC content, and then explore the optimization strategy of the PUGC model, which provides effective methods and tools for the further optimization of the construction of PUGC on the comprehensive video community platform, and also provides a reference for the academic community to conduct in-depth research on PUGC communication.